2020
DOI: 10.1111/jcmm.15737
|View full text |Cite
|
Sign up to set email alerts
|

IL‐38: A novel cytokine in systemic lupus erythematosus pathogenesis

Abstract: Systemic lupus erythematosus (SLE) is a complex, inflammatory autoimmune disorder. Genetics and environmental factors interacted in occurrence of the disease. It is characterized by dysregulation of autoantibodies, complement system and inflammatory cytokines. 1 Cytokine-mediated immunity has been found to perform significantly in SLE pathogenesis. 2,3 Interleukin-38 (IL-38, previously called IL-1F10) belongs to the IL-1 family and has been identified in recent years. The human IL-38 gene has 4 exons and is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
0
19
2
Order By: Relevance
“…The levels of this cytokine were higher in active patients and associated with multiple clinical and laboratory parameters including arthritis, pericarditis, haematuria, proteinuria, pyuria and anti-dsDNA. Correlation analysis indicated that plasma IL-38 correlated positively with SLEDAI and negatively with C3 and C4 levels [ 88 ].…”
Section: Il-1 Il-18 and Il-38mentioning
confidence: 99%
“…The levels of this cytokine were higher in active patients and associated with multiple clinical and laboratory parameters including arthritis, pericarditis, haematuria, proteinuria, pyuria and anti-dsDNA. Correlation analysis indicated that plasma IL-38 correlated positively with SLEDAI and negatively with C3 and C4 levels [ 88 ].…”
Section: Il-1 Il-18 and Il-38mentioning
confidence: 99%
“…IL-38 has been considered as an IL-1 family antagonist for its high homology to IL-36Ra and IL-1Ra [ 10 ]. Most studies conclude that IL-38 exerts anti-inflammatory effects in several autoimmune diseases, including RA, AA, and SLE [ 13 15 ]. On the contrary, several other studies have shown that IL-38 can act as a pro-inflammatory factor, and it can modestly enhance candida-induced IL-22 and IL-17 expression in human PBMCs at a higher concentration [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-38 is an abundant, ubiquitously expressed cytokine, which can be secreted by fibroblast-like synoviocytes, peripheral blood mononuclear cells (PBMCs), keratinocytes, epithelial cells, and various immune cells, such as B cells, natural killer (NK) cells, macrophages, and dendritic cells (DCs) [ 11 , 12 ]. Abnormal expression of IL-38 has been found in many inflammatory diseases, including rheumatoid arthritis (RA), allergic asthma (AA), and systemic lupus erythematosus (SLE) [ 13 15 ]. In addition, elevated serum IL-38 levels at baseline can be used to predict virological response in telbivudine-treated patients with chronic hepatitis B [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, specific datas were not shown. Furthermore, Xu et al (2020a) reported that compared with volunteers, the mRNA level of IL-38 in peripheral blood mononuclear cells (PBMCs) of SLE patients was increased. In vitro , silencing endogenous IL-38 in PBMCs caused an apparent augment in the lupus-associated mediators IL-6 and APRIL (a proliferation-inducing ligand) ( Fanouriakis et al, 2021 ).…”
Section: The Function Role Of Il-38 In Autoimmune Diseasesmentioning
confidence: 99%